Flat-panel display technologies : Japan, Russia, Ukraine, and Belarus - Tannas, Lawrence E. (Noyes Publications, 1995)
Large scale manufacturing of liquid crystal flat panel displays (LCDs) by Japan brought the world's attention to the existence of an enormous market potential exists when there are alternatives to the cathode ray tube (CRT). The Japanese have recognized that new display technologies are critical to making their products highly competitive in the world market. The CRT is losing market share to the solid-state flat panel display. Japan currently holds 90% of the market, and this book outlines opportunities in the former Soviet Union, where companies with the necessary technology are seeking partners, investment, and manufacturing opportunities. Entire cities that were once not even on the map due to their military mission, are now appearing, filled with state-of-the-art electronic technology. The book is developed from the reports issued by investigators based on their field visits to 33 sites in Japan, and 26 sites in Russia, Ukraine, and Belarus.